In vitro methane production from silages based on Cenchrus purpureus mixed with Tithonia diversifolia in different proportions - María Alexandra Huertas González (Acta Scientiarum. Animal Sciences, 2021)
Climate change (CC) affects food production, mainly those based on livestock systems. Producers must identify adaptation strategies to ensure the production, during periods of drought, and lack of forage. Besides contributing to CC, high emissions of ruminal methane (CH4) are energy loss potentially usable for livestock production. The objective was to estimate in vitro ruminal gas production (RGP) and determine the CH4 emissions from silages. Treatments were made with forage of Cenchrus purpureus mixed with Tithonia diversifolia T1= C.purpureus at 100%; T2= C.purpureus/ T.diversifolia in 33/67 percent ratio; T3= C.purpureus/ T.diversifolia 67/33; and T4= T.diversifolia at 100%. Samples of silages were analyzed, and they were inoculated with strains of Lactobacillus paracasei (T735); then they were fermented in vacuum-sealed bags for 67 days. RGP and CH4 were measured at 2, 4, 8, 12, 18, 24, 30, 36, and 48 hours. Additionally, modeling of CH4 production kinetics was conducted, using different equations. The results indicate that the highest cumulative CH4 production was for T1. This kinetics was represented using the Gompertz model. In conclusion, the inclusion of T.diversifolia to C.purpureus silages contributes to the decrease of methane at the ruminal level, which constitutes an adaptation practice at climate change.